2021
DOI: 10.3389/fcell.2021.727037
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-Responsive Transcription Factor Krüppel-Like Factor 9 Regulates fkbp5 and Metabolism

Abstract: Krüppel-like factor 9 (Klf9) is a feedforward regulator of glucocorticoid receptor (GR) signaling. Here we show that in zebrafish klf9 is expressed with GR-dependent oscillatory dynamics in synchrony with fkbp5, a GR target that encodes a negative feedback regulator of GR signaling. We found that fkbp5 transcript levels are elevated in klf9–/– mutants and that Klf9 associates with chromatin at the fkbp5 promoter, which becomes hyperacetylated in klf9–/– mutants, suggesting that the GR regulates fkbp5 via an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 74 publications
3
21
0
Order By: Relevance
“…Experiments with the knockout line revealed that the defensive/pro-inflammatory transcriptomic response to chronic cortisol that we had previously reported in wildtype larvae was absent in klf9 −/− mutants (Gans et al, 2020), which in contrast responded by upregulating genes involved in glycolysis and related metabolic pathways (Gans et al, 2021). Furthermore, we found that klf9 expression is both oscillatory and synchronous with that of fkpb5, which appears to be directly repressed by Klf9 (Gans et al, 2021). Together these results suggest that klf9 is a key node in the gene regulatory network regulating GC responsivity (Figure 5), both by co-regulating fkbp5 in an incoherent feedforward loop with the GR, and by repressing glycolytic gene expression (possibly also via incoherent feedforward regulation) in a way that is predicted to favor flux through the pentose phosphate pathway (Gans et al, 2021).…”
Section: Evidence That Klf9 Is a Key Regulator Of Glucocorticoid Signalingmentioning
confidence: 71%
See 4 more Smart Citations
“…Experiments with the knockout line revealed that the defensive/pro-inflammatory transcriptomic response to chronic cortisol that we had previously reported in wildtype larvae was absent in klf9 −/− mutants (Gans et al, 2020), which in contrast responded by upregulating genes involved in glycolysis and related metabolic pathways (Gans et al, 2021). Furthermore, we found that klf9 expression is both oscillatory and synchronous with that of fkpb5, which appears to be directly repressed by Klf9 (Gans et al, 2021). Together these results suggest that klf9 is a key node in the gene regulatory network regulating GC responsivity (Figure 5), both by co-regulating fkbp5 in an incoherent feedforward loop with the GR, and by repressing glycolytic gene expression (possibly also via incoherent feedforward regulation) in a way that is predicted to favor flux through the pentose phosphate pathway (Gans et al, 2021).…”
Section: Evidence That Klf9 Is a Key Regulator Of Glucocorticoid Signalingmentioning
confidence: 71%
“…Given the ease of adding treatments to water, zebrafish are increasingly used in screening for toxicant effects. In a screening of steroid hormones, modest decrease in activity level was found in larvae treated with GCs, along with a significant increase in trough expression level of circadian genes including per1a and nr1d2a (Zhao et al, 2018), two genes we have also found increased by chronic cortisol exposure (Gans et al, 2020(Gans et al, , 2021. Another group found that environmentally relevant concentrations of cortisol and the synthetic prescription GC clobetasol propionate impacted larval muscle and heart function, as well as expression of genes involved in immunity, glucose metabolism, development, and the circadian clock (Willi et al, 2018).…”
Section: Studies In Zebrafishmentioning
confidence: 77%
See 3 more Smart Citations